Albert Hien : Museo Grosso. (Heidenheim : Kunstmuseum Heidenheim, 1994)
Slipcase with 3 mini-slipcases (all of white board) and a catelogue of the exhibition. The slipcases each contain fold-out poster with a ready to built figure what represents a designed model of the theme- exhibition. The are three theme-exhibitions: respectively: Museum of nature and science with a equally named design; II Ortobotanico with the design "Früchte" and III . Museum der Technik.
Albert Hien : Museo Grosso, Museum der Technik, Kunstmuseum Heidenheim, 19. Juni - 28. August 1994 .
Duits
kunstcatalogus
Keywords: Hien, Albert